Characterisation of Seismicity of the Azores Archipelago: An Overview of Historical Events and a Detailed Analysis for the Period 2000–2012 - Fontiela, Joao (2018)
The Azores Archipelago is located in the Middle Atlantic Ridge, at the Triple Junction formed by the contact of the Euro-Asiatic, the Nubia (African) and the American plates (see also Vogt and Jung, Chapter “The “Azores Geosyndrome” and Plate Tectonics: Research History, Synthesis, and Unsolved Puzzles”). Its seismicity rate is very high with earth- quakes with relatively low magnitude, defining quite well the contact regions. This chapter gives an overview of the existing historical and instrumental catalogues, describes the seismic- ity of the region essentially since early 1915, and analyses in more detail the characteristics of the recorded data in the period 2000–2012. The spatial variations of the minimum magni- tude of completeness (Mc) as well as the b-value is studied for this period within the stripe of observed seismicity which contains the alignment of the Archipelago islands. A preliminary interpretation of the Mc and b-values is made keeping in mind the geolog- ical transition between the Gloria fault to the East and the Mid-Atlantic Region to the West.